The skills that matter : teaching interpersonal and intrapersonal competencies in any classroom - Noonan, Patricia M.; Erickson, Amy S. Gaumer (Corwin, a SAGE Company, 2018)
The Skills That Matter aims to prepare middle and high school teachers to increase students' intrapersonal and interpersonal competencies school-wide. This eight-chapter book presents competency-specific information and tools teachers can use to support middle and high school students' development of six key intrapersonal and interpersonal competencies. Competencies covered in this book include self-regulation, goal-setting, self-efficacy, assertiveness, conflict management and networking.